Business Strategy In The Halal Industry (The Use Of Digital Ecosystems In Introducing Indonesia As The World's Halal Industry) - Akmal Akmal; Ahmad Effendi (International Journal of Economics, Business and Innovation Research, 2023)
This research provides an overview of how business strategies in the view of Islam which of course in the process of running a business must be accompanied by sharia rules. The world is becoming more globalised, with businesses producing products that are now considered halal. This sector has a huge impact on the world economy, and the halal market is now dominant in the commercial world. With a huge potential market size, Muslim countries currently have more than 1.6 billion consumers, supporting the growth of halal lifestyles among the non-Muslim population. To grow and compete in the global market for halal products, Indonesia needs a well-executed strategy that capitalises on the development of the digital ecosystem. One way to achieve this is by encouraging businesses that are acceptable and valued by society and can be seen as export commodities that can drive the growth of trade and industry-related sectors, which in turn will help increase national income. A specific strategy is needed to develop the halal industry in Indonesia, and one important way to achieve this is by capitalising on the growth of the digital ecosystem.